Teatro van: teatro escolar como um espaço pedagógico. - Pires, Berenice Alves Mendes (2024)
This research is part of an experience with children, which brings together two skills: transporter and artist and, thus, facilitates the learning of children who use my services, making my profession more pleasurable for me and transport more meaningful for their children. children. To develop this research, the following objectives were formulated: a. General: propose school transport (van) as an inclusive and educational space for all children and b. Specific: Facilitate children’s free expression within a space in which they feel free; develop a creative and spontaneous pedagogical proposal that facilitates the learning of students who have attention difficulties. As a theoretical reference used primarily as practices and theories by Célestin Freinet, as well as articles by researchers on the topic of tour classes. The methodology used is an exploratory research that shows a work experienced over ten years ago and that I believe to find, through research, contributions to deepen the studies and the relationship with this object, the material used is the children's reports and their own experience. with them and the data will also be analyzed in light of the bibliography that serves as theoretical support for the analysis, but as it is an exploratory research, bringing experience (mine and the students') is very significant, coherent with the theme and the chosen reference is the crucial point of this research. I believe that this research brings many contributions to those interested in the topic, as school transport is a necessity in the daily lives of parents and students. Combining this with educational practice not only makes the activity more enjoyable but also contributes to children's meaningful learning. outside the classroom.